Reinforcement effects of nano-modified coir fibres on lime-treated marine clay - Anggraini, Vivi (2015)
Marine clay soils under land-based structures develop shrinkage cracks due to the uneven distribution of moisture. Treatment of marine clay soils with lime is one of the widely used methods. However, the soils treated with lime will cause to brittle failure. Therefore, to improve the mechanical properties of treated soil, the lime treatment technique combined with inclusion of randomly distributed tensile reinforcement elements such as natural fibres (e.g., coir fibre) were used. However, the mechanical performance of the treated soil depends not only on the nature of the soil, moreover on the mechanical properties of the fibre as well the interaction between the fibre and the lime-treated soil. This research was developed to further increase the performance of coir fibre in limetreated soil as pile-supported earth platform. A nano impregnation method was applied through chemical treatment with different chemicals including CaCl2, MgCl2, AlCl3 and FeCl3 in order to impregnate fibres with nano-particles. To confirm the alteration of morphology in the fibres and understand the underlying mechanisms of chemically treated fibres, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) tests were performed. Furthermore, the mechanical properties of the composites were assessed. Unconfined compressive strength tests, indirect tensile strength tests, flexural strength tests, and triaxial compressive strength tests were carried out on original soil, lime-treated soil, and lime-treated soil reinforced with nano-treated and untreated fibre. Moreover, a durability test was conducted to scrutinize the change in the strength of the reinforced soil. Finally, the experimental results were used in a numerical analysis using commercially available software (ABAQUS CAE) to investigate the performance of the proposed treatment as pile supported earth platform. The physical model experiments were performed to validate numerical model. The results revealed that the nano impregnation of fibres increased the tensile strength up to 200% compared with untreated fibres. The fibres modified with Ca(OH)2 showed higher mechanical performance compared with the fibres modified by Mg(OH)2,Al(OH)3, and Fe(OH)3. The SEM/EDX results showed that cellulosic pores of the fibres were filled with Ca nano-sized crystals ranging from 25 to 150 nm. The mechanical performance of the treated soil increased when chemically treated fibres were used. The compressive strength, indirect tensile strength, and flexural strength of the treated soil increased by 66, 122, and 60% when Ca(OH)2-treated fibres were used compared with those of limed soil reinforced with untreated fibres. Moreover, the addition of nano impregnated fibres using Ca(OH)2 increased the shear strength parameters of marine clay soil with increases in the level of confining pressure and consequently led to a more ductile behaviour. The numerical analyses show the importance of the mechanical properties of the treated soils are effective in reducing the differential settlement up to 50% when the height of the earth platform used is 0.3 m. The research is important in that it confirms that the nano modification technique can not only increase the mechanical performance of the coir fibres but also improve the interfacial mechanical interactions between the fibre surface and soil particles, resulting in a higher performance of the composites used as a pile-supported earth platform.